Economic Evaluation of Gold Nanoparticle (AuNP) Production Using Laser Ablation Synthesis Method - Salma Rahmadianti; Kanthi Pawening Tyas; Permata Maratussolihah; Gabriela Chelvina Santiuly Girsang; Asep Bayu Dani Nandiyanto (Urecol Journal. Part D: Applied Sciences, 2021)
Gold nanoparticles are very useful in various fields such as photoacoustic imaging microscopy, biotechnology, optoelectronics, and biomedicine. So the production of gold nanoparticle synthesis needs to be developed to an industrial scale. The purpose of this study is to determine the feasibility of the gold nanoparticle synthesis project using the laser ablation method on large-scale based on economic aspects. Several economic evaluation parameters are analyzed to inform the potential production of AuNP, such as GPM (Gross Profit Margin), BEP (Break-Even Point), CNPV (Cumulative Net Present Value), PBP (Payback Period), and PI (Profitability Index). The results showed that the production of AuNP nanoparticles was so prospective. Technical analysis to produce 100 g of AuNP nanoparticles per day shows the total cost incurred by the production process is 2,323,180 USD per year. PBP analysis show that investment will be profitable after more than 2.2 years. This project can compete with PBP capital market standards because of the short investment returns. To ensure the feasibility of a project, the project is estimated from ideal conditions to the worst case in production, including labor, sales, raw materials, utilities, and external conditions.